Questioning discrimination through critical media literacy. Findings from seven European countries. (July 2016) - Ranieri, Maria; Fabbro, Francesco
This paper presents the main findings of an action-research study that took place in seven European countries in order to develop effective educational responses to prevent and combat discrimination. The study entailed the design of media and citizenship education activities, their implementation in the different educational contexts and the evaluation of their effectiveness in raising young people's awareness of discrimination. The results of the study shed light both on the advantages and constraints of educational practice, variations that often depend on the specific cultural and social context. On the one hand, the analysis and the evaluation of educational experiences suggest that critical media literacy can enable the development of critical reading/viewing skills as well as acts of participatory and inclusive citizenship that question derogative and essentialist media representations of the Other. On the other hand, the results highlight the difficulty of promoting young people's awareness of discrimination through active methods of teaching and learning or through media content which is far from young people's experience, interests and concerns.